Pengembangan E-Modul Kesetimbangan Kimia Berbasis Pendekatan Saintifik untuk Kelas XI SMA/ MA - Asmiyunda Asmiyunda; Guspatni Guspatni; Fajriah Azra (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
The 2013 curriculum recommends scientific approach in learning and expects students to be skilled in using ICT. The research aim to develop a chemical equilibrium e-module based on scientific approach for XI SMA/ MA class and to determine validity and practicality level. This research is Research and Development (R&D) with 4-D model. Validity test was done by 3 chemistry lecturers at FMIPA UNP, 1 multimedia lecturer at FT UNP, 2 chemistry teachers at SMAN 1 Pariaman and 1 chemistry teacher at SMAN 7 Padang. Practicality test was done by 2 chemistry teachers at SMAN 1 Pariaman, 1 chemistry teacher at SMAN 7 Padang and 30 XII MIPA 7 SMAN 1 Pariaman students. The instrument was validity and practical questionnaire and data was analyzed by Cohen Kappa formula. This study produced a chemical equilibrium e-module based on scientific approach with an average kappa moments 0,81 which is very high level of validity. The results of the teacher practicality test and the students practicality test obtained an average of kappa moments in a sequence of 0,85 and 0,84 with a very high level of practicality Keywords: e-module, scientific approach, 4-D models, chemical equilibrium